Formulación de una estrategia de mejora de atención al cliente que permita la satisfacción y fidelización de clientes para la empresa AGL Vans Tours del sector de servicio de transporte especial (2021)
The text described here will take special focus on customer service and the most relevant models of care over the years that applies to this type of commercial interaction, and will take as an example the company AGL Vans Tours, which is part of Colombia's special land transport service sector in order to develop a customer service model that is applicable , by means of its respective justification and definition of the scope of the model, in addition to establishing the criteria to be assessed in the model. Prior to this, the functions of the models are contextualized and mentioned the most important characteristics of which have already been developed and implemented, and from this is done the construction of the customer service model for the company AGL Vans Tours, which has as its firm purpose to increase customer satisfaction and acquisition, and therefore increase the levels of competitiveness in the market of Colombia's special land transport service sector.